Significance Level of Pleural Fluid Tissue Inhibitor Metalloproteinase-1 (TIMP-1) and Glucose Levels as Biomarkers of Malignant Pleural Effusion - Michaela, Cleine; Putra, Ngakan Putu Parsama; Djajalaksana, Susanthy; Setijowati, Nanik; Listyoko, Aditya Sri (Jurnal Respirasi, 2025)
Introduction: Distinguishing between malignant and non-malignant pleural effusions is often challenging due to overlapping biochemical profiles. Conventional diagnostic methods, including cytology and biopsy, are limited by their invasive nature, high costs, and potential complications. Emerging biomarkers, such as tissue inhibitor of metalloproteinase-1 (TIMP-1) and pleural fluid glucose levels, show promise as alternative diagnostic tools, but their clinical utility requires further validation. This study investigated the diagnostic value of TIMP-1 and pleural fluid glucose levels in differentiating malignant from non-malignant pleural effusions and explored their correlation in malignant cases. Methods: This cross-sectional analytical study included patients with exudative pleural effusion, categorized as malignant or non-malignant based on cytology and/or biopsy results. Biomarker levels of TIMP-1 and pleural fluid glucose were measured using enzyme-linked immunosorbent assay (ELISA) and biochemical analysis. Diagnostic thresholds for both biomarkers were determined using receiver operating characteristic (ROC) curve analysis. Results: Among 88 patients studied (33 malignant, 55 non-malignant), pleural fluid glucose levels were significantly lower in malignant cases (55.97 vs. 93.71 mg/dL; p=0.001), while TIMP-1 levels were notably higher (13.88 vs. 13.34 pg/mL; p<0.001). Tissue inhibitor of metalloproteinase-1 demonstrated superior diagnostic accuracy (86.5%) compared to glucose (70.6%) and the combined biomarker model (76.5%), with the sensitivity and specificity of 84.8% and 83.6%, respectively. Conclusion: Elevated TIMP-1 levels and reduced pleural fluid glucose levels are promising diagnostic biomarkers for malignant pleural effusion (MPE). Tissue inhibitor of metalloproteinase-1 exhibited the highest diagnostic accuracy, highlighting its potential as a non-invasive diagnostic tool in clinical practice.